2014
DOI: 10.4293/108680813x13753907291233
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Predictability of Hiatal Hernia Prior to Gastric Band Surgery

Abstract: Background:Hiatal hernia (HH) is closely associated with morbid obesity. There is controversy over the need for preoperative imaging before laparoscopic adjustable gastric band placement. The aim of this study is to determine the predictive value of preoperatively diagnosing HH with upper gastrointestinal (UGI) series imaging.Methods:A retrospective review of a single surgeon's experience with laparoscopic adjustable gastric band placements was performed. All patients received a preoperative UGI series. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Furthermore, the finding during the operation still has the most accurate evidence. In the study of Broucek JR, et al [16] showed that UGI series have poor positive and negative predictive values in preoperatively diagnosing HH. Also, patient symptoms were different subjectively and anti-reflux medication did not match with radiologic or intraoperative findings of HH [17].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the finding during the operation still has the most accurate evidence. In the study of Broucek JR, et al [16] showed that UGI series have poor positive and negative predictive values in preoperatively diagnosing HH. Also, patient symptoms were different subjectively and anti-reflux medication did not match with radiologic or intraoperative findings of HH [17].…”
Section: Methodsmentioning
confidence: 99%
“…Распространенность данного заболевания среди взрослого населения планеты составляет 21-47%, в пожилом возрасте может достигать 50% [8][9]. С развитием рентгенологической техники и появлением компьютерной томографии стало возможным не только точно диагностировать ГПОД, но и измерять дефект пищеводного отверстия диафрагмы (далее -ПОД), расстояние между диафрагмальными ножками в разных проекциях и состояние диафрагмы [10][11][12][13][14]. В публикациях ряда авторов имеются данные о прижизненной компьютерно-томографической анатомии кардиоэзофагеального перехода в норме и при гастроэзофагеальной рефлюксной болезни, при этом нет детальных морфометрических параметров структур кардиоэзофагеального перехода при ГПОД [15][16].…”
unclassified